Feeding Cultured Taxus Cells with Early Precursors Reveals Bifurcations in the Taxoid Biosynthetic Pathway - Ketchum, Raymond E.B. (2006)
Feeding studies with Taxus suspension cells employing labeled 5α-hydroxytaxadiene and 5α,10β-dihydroxytaxadiene, and the corresponding 5α-acetate esters, demonstrated that acetylation at C5 of the monool precursor promotes the formation of 14β-hydroxy taxoids, such as taxuyunnanine C, at the expense of 13α-hydroxy taxoids, including Taxol and its congeners, but that the major bifurcation in taxoid biosynthesis, toward 13α- or 14β-hydroxy taxoids, occurs after 10β-hydroxylation of the taxane core.